PERDAGANGAN PEREMPUAN (TRAFFICKING IN WOMEN) DALAM PERSPEKTIF HUKUM ISLAM - Rahmawati, Rahmawati (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2006)
Trafficking in women is a growing issue in Indonesia and elsewhere from time to time. The majority of the victims are trafficked, generally, for sexual exploitation. This sort of human trafficking is forbidden by religion and is categorized as a violence due to its undesirable impacts. The victims are forced to have sexual activity without marriage (legal marriage). In Islam, women traficcking issue is discussed in Fiqh because what is sold or taken from the victims is their service. However, this kind of transaction is considered as unlawfull transaction as it is not lawfully regulized ( ghairu masyru’).